The Presence and Absence of the Past: Sites of Memory and Forgetting in F. C. Delius's Die Flatterzunge - Carol Anne Costabile-Heming (Studies in 20th & 21st Century Literature, 2004)
Perhaps no site better embodies the juxtaposition of the German past with the challenges of the present and prospect for the future than Berlin. For the city of Berlin, the past (Third Reich, Holocaust) is simultaneously present and absent from view…
Keywords: Presence; Absence; Past; Sites of Memory; Forgetting; F. C. Delius; Die Flatterzunge; German past; present; present challenges; prospect for the future; city of Berlin; Berlin; capital city; Holocaust; Third Reich; World War II; Second World War